Temperature and salinity data collected using thermosalinograph [TSG] during the Tara Pacific Expedition 2016-2018 - Gilles Reverdin; Hervé Le Goff; Guillaume Bourdin; Fabien Lombard; G Gorsky; Clémentine Moulin; Guillaume Iwankow; Emilie Boissin; Julie Poulain; Sarah Romac; Sylvain Agostini; Bernard Banaigs; et al. (PANGAEA, 2022)
The Tara Pacific expedition (2016-2018) sampled coral ecosystems around 32 islands in the Pacific Ocean, and sampled the surface of oceanic waters at 249 locations, resulting in the collection of nearly 58,000 samples. The expedition was designed to systematically study corals, fish, plankton, and seawater, and included the collection of samples for advanced biogeochemical, molecular, and imaging analysis. Here we provide the continuous dataset originating from the thermosalinograph [TSG] instrument acquiring continuously during the full course of the campaign. Surface seawater was pumped continuously through a hull inlet located 1.5 m under the waterline using a membrane pump (10 LPM; Shurflo), circulated through a vortex debubbler, a flow meter, and distributed to a number of flow-through instruments. A thermosalinograph [TSG] (SeaBird Electronics SBE45/SBE38), measured temperature, conductivity, and thus salinity. Salinity measurements where intercalibrated against unfiltered seawater samples [SAL] taken every week from the surface ocean, and corrected for any observed bias. Moreover, temperature and salinity measurements were validated against Argo floats data collocated with Tara.